A design of impedance transformer with tunable center frequencies using filter synthesis approach. Issue 8 (28th April 2022) - Chaudhary, Girdhari; Jeong, Yongchae
Abstract: Microwave impedance transformer (IT) with center frequency tunable capability is one of great research issue for better utilization of frequency spectrum resources and system miniaturization of next generation wireless communication systems. This article presents a filter synthesis approach for designing IT with center frequency tunable capability using single dc‐bias controlled tunable resonators. The proposed IT provides bandpass filtering response and is designed by properly coupling quarter‐wave tunable resonators with alternate J‐ and K ‐inverters. The J ‐inverters are realized using a parallel‐coupled line, whereas K ‐inverter is implemented with T‐type short‐circuited TL. Using filter theory, analytical design equations are derived to calculate the circuit parameters. The center frequency of the proposed IT is tuned over a wide frequency tuning range (FTR) by changing the varactor diode capacitance of quarter‐wave resonators. For experimental demonstration, a prototype of 25‐to‐50 Ω IT is designed, simulated, and measured. The measured results confirmed that the center frequency of the proposed IT is tuned from 2.05 to 2.91 GHz (860 MHz or 34.68% FTR) with an insertion loss variation of 2.57 to 1.76 dB.